A review of psychocutaneous disorders from a psychotherapeutic perspective-Toolkit for the dermatologist - Mary Zagami; Edward Klepper; Eric Wienecke; Maria Andrzejewski; Ahmed Sikder; Ali Ahmed; Howard Robinson (Wiley, 2023)
Abstract Introduction The study of psychocutaneous disorders requires a multidisciplinary approach. It is of paramount importance that dermatologists understand the psychiatric premise for these disorders. Mental health professionals can also benefit from a better understanding of the dermatologic manifestations of psychiatric disorders they may encounter in their practice. Aim The aim of this study is to elevate the level of understanding regarding psychotherapeutic treatment of psychocutaneous disorders. Methods We performed a literature review using the major databases. Four researchers reviewed English, full text, peer‐reviewed articles that were published after 2000 using our specific search terms and inclusion/exclusion criteria. Results The majority of psychocutaneous disorders seem to be clustered among three DSM‐5 disorders: depressive disorders, anxiety disorders, and obsessive‐compulsive related disorders. Conclusions Better recognition of the underlying psychiatric comorbidities may lead to improved patient outcomes.